KEY FACTORS IN THE DEVELOPMENT OF COMMUNICATION BETWEEN LOCAL GOVERNMENTS AND THE PUBLIC IN THE CONTEXT OF DIGITAL TRANSFORMATION OF TERRITORIAL COMMUNITIES - SERDYUK, Olga; KANIVETS, Dmytro; PROTSENKO, Yelyzaveta (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article outlines the factors of development of communication between local self-government bodies and the public, taking into account digital maturity and areas of digital transformation of territorial communities. It is established that digitalization gives a new character to the communicative interaction of local self-government bodies with the public: it ensures openness of the community, two-way communication between the leadership of the territorial community and residents, understanding of their needs and requests, and search for the best ways to solve them. It is noted that the Index of Digital Transformation of Territorial Communities can be used as a basis for strategic planning of local development in the field of digitalization and response to the needs and changes in the community, identification of priority areas of digitalization, financing of relevant programs, making informed decisions and developing communication with residents. he results of the pilot measurement of the Index of Digital Transformation of Territorial Communities based on the self-assessment of local governments in Ukraine and, in particular, in Poltava region are studied. It is noted that none of the territorial communities of Ukraine has a transformational and proactive level of digital maturity, the TOP-100 most digitized territorial communities have a promising or basic level, and the rest have a starting level. It has been found that in Poltava region, the highest levels of the digital transformation index and all its structural elements are in territorial communities with a population of more than 50 thousand people, and the level of financial capacity of the territorial community is a significant factor in digital transformation only for territorial communities characterized by a high level of financial capacity (15 points or more). The factors of development of communication between local self-government bodies and the public are determined, taking into account the most important indicators of the Index of Digital Transformation of Territorial Communities, which simultaneously determine the effectiveness of communication interaction.
Keywords: public administration; local self-government; territorial community; digital transformation; communications with the public; electronic interaction